2018
DOI: 10.1016/j.nonrwa.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Global dynamics of an SIR epidemic model with nonlocal diffusion

Abstract: In this paper, we are concerned with the global asymptotic stability of each equilibrium of an SIR epidemic model with nonlocal diffusion. Under the assumption of Lipschitz continuity of parameters, the eigenvalue problem associated with the linearized system around the disease-free equilibrium has a principal eigenvalue corresponding to a strictly positive eigenfunction. By setting the eigenfunction as the integral kernel of a Lyapunov function, we prove the global asymptotic stability of the disease-free equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 50 publications
0
41
0
1
Order By: Relevance
“…Let λ 0 (η) be the principal eigenvalue of problem (23). There exists an enough small constant η * ∈ (0, 1), so λ 0 (η * ) > 0, and S 0 (x) − η * > 0 for all x ∈ .…”
Section: Uniform Persistencementioning
confidence: 99%
See 1 more Smart Citation
“…Let λ 0 (η) be the principal eigenvalue of problem (23). There exists an enough small constant η * ∈ (0, 1), so λ 0 (η * ) > 0, and S 0 (x) − η * > 0 for all x ∈ .…”
Section: Uniform Persistencementioning
confidence: 99%
“…Although convenient transportation can bring great convenience to people's travel, it also makes the epidemic to spread to other areas quickly. After analysing the number of patients with a disease in different cities, many researchers found that the number of patients was closely related to the mobility of population, and proposed different types of reactiondiffusion epidemic models on this phenomenon (see, for example [5,23,25,44,47,48]). Especially, Yang et al [48] studied a seasonal brucellosis SIV epidemic model with nonlocal transmissions and spatial diffusions.…”
Section: Introductionmentioning
confidence: 99%
“…Then virions arrive at location from other places at rate ∫ Ω ( − )V( ) . Based on peculiar features of the nonlocal diffusion operators, models in ecology [13][14][15], in epidemiology [16][17][18][19], and even in materials science [20,21] have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…is the rate at which they leave position x to reach any other position. For example, in water-biomass models the kernel function J(x−y) means the probability per unit length of seeds originating at the point y being dispersed to point x [1,12,30,31]; in epidemic models the kernel function J(x−y) weights the contributions of the susceptible/infective/recovered individuals at location y to the susceptible/infective/recovered individuals at location x [4,26,37,38]. In recent years, the nonlocal dispersal has attracted the attention of a great number of investigators [2,3,7,8,9,10,14,20,21,36] and the references therein for more details.…”
mentioning
confidence: 99%
“…Thus it is difficult to analyze the global dynamics of these nonlocal models. Thanks to [26,37,38], by Lyapunov functional and LaSalle's invariance principle, some results about the existence, uniqueness and stability of steady states of nonlocal SIS epidemic models have been obtained if the dispersal spread is held fixed, i.e. d…”
mentioning
confidence: 99%